Introduction: Educating Newcomers for the Modern Welfare State: Danish Frontline Organisations as Educational Sites and Drivers of Knowledge from the Late 1960s to the Late 1990s - Buchardt, Mette; Breidahl, Karen Nielsen (Nordic Journal of Educational History, 2026)
Welfare-state education politics concerning migrants have mainly been studied inside the formal education system in historical and social science research. The special theme that this article introduces takes a broader view on “education” by directing attention to what we term “educational integration policies and practices” in the context of the Danish welfare state. Thereby we also suggest a broader scope for the history of education beyond the formal education system. The overall term Welfare state refers to a variety of welfare-state arrangements which have served an important role in educating newcomers about the welfare state, namely asylum centres, language teaching of adult newcomers, and social housing. The special theme directs attention to organisational frontline practices of these welfare-state arrangements, focusing on how educational integration practices were formed and shaped and became knowledge drivers for broader policy making in the formative years of Danish integration policy, beginning with the guest worker era in the late 1960s and continuing in the following decades. This introduction article presents the analytical and methodological background of the articles.